To solve the equation \( ax + by = c \) for \( x \), you would isolate \( x \) on one side of the equation. Here are the steps:
-
Start with the equation: \[ ax + by = c \]
-
Subtract \( by \) from both sides: \[ ax = c - by \]
-
Divide both sides by \( a \) (assuming \( a \neq 0 \)): \[ x = \frac{c - by}{a} \]
So the solution for \( x \) in the equation \( ax + by = c \) is: \[ x = \frac{c - by}{a} \]
If you have specific answer choices (A, B, C, D), please provide them, and I can indicate which one is correct!